Labor and health of undocumented migrant women: evidence from a large primary care outpatient clinic in Milan, Italy - Devillanova, Carlo; Spada, Anna (Frontiers in Human Dynamics, 2025)
BackgroundUndocumented migrant women face compounded risk exposure stemming from precarious living and working conditions, legal exclusion, and barriers to healthcare access. Empirical evidence linking their sociodemographic status and health trajectories remains scarce, particularly in Italy and Europe.MethodsWe conducted a retrospective observational study of 3,000 women aged ≥18 who attended Naga—a nonprofit primary-care clinic for undocumented migrants in Milan—between January 1, 2022 and February 20, 2025. Integrated records combine first-visit sociodemographic data with ICD-10—coded diagnoses at each consultation (7,463 total visits). We summarize ICD-10 chapter distributions across all consultations to characterize the clinic's diagnostic profile; describe sociodemographic characteristics using the single-visit cohort and the first- visit subsample (where clinical and demographic data are temporally aligned); trace diagnostic trajectories among returning patients; and employ multivariate logistic regression on the first-visit group to assess the extent to which age, education, and occupation correlate with diagnosis at entry.ResultsNearly two-thirds of women had arrived within 12 months and 55% were unemployed, despite over 60% having ≥ upper-secondary education. Preventive and reproductive care (ICD-10 Chapter XXI) accounted for ~16% of visits, followed by musculoskeletal (11%) and genitourinary (10%) disorders. Chronic conditions (endocrine, circulatory, chronic respiratory/genitourinary) comprised 15.7% of visits, and 14.6% of women received a chronic diagnosis over follow-up. Compared with the full sample, first visits concentrate more on preventive/reproductive care—Z30 34.6% vs. 31.8%; Z03 18.1% vs. 13.4%—and show fewer chronic and mental-health diagnoses (Chapter V 2.8% vs. 4.2%). Age emerged as the dominant predictor: older women exhibited sharply higher odds of chronic-disease chapters (e.g., OR 6.1 for endocrine; OR 30.7 for circulatory in those ≥65).ConclusionsThis large clinic-based cohort reveals how undocumented migrant women initially seek reproductive and acute care, and over subsequent contacts they are more likely to receive chronic and mental-health diagnoses, in a context of precarity. Extending primary-care enrolment (GP access) could lessen structural disadvantages and strengthen continuity of care. Future research should assess whether, and to what extent, labor-market trajectories are associated with health outcomes, to inform comprehensive policy responses.